DETECTION OF BACTERIA Esherichia coli SEROTYPE O157 ON PORK FROM PORK TRADER IN DENPASAR CITY - Hendrayana, Made Agus; Putra Pinatih, Komang Januartha; Yelly, Amy (Medicina, 2012)
Escherichia coli (E.coli)  is the pathogenic bacteria which commonly associated with intestine and kidney infection in human. One of the strain of zoonotic E.coli serotype O157. Human and cattle, mostly swine are predominant reservoirs for E. coli O157. Swine butchering in Bali specifically in Denpasar is increasing each year. The aim of this study was to identify E.coli serotype O157 in pork in Denpasar. They were 31 samples of pork taken from different butchers in 24 traditional markets and seven supermarkets that entirely located in Denpasar. Total Plate Count (TPC) method was used to count E.coli and  coliform colonies. Plate Count agar (PCA), Eosin Methylene Blue Agar (EMBA) and selective Sorbitol MacConkey Agar (SMAC) were applied in this study as well. Metallic green colonies were found and taken for Gram staining then were inoculated on the media of biochemical test (IMViC). Next, the colonies were inoculated on the media of SMAC and observed for existence of colorless colonies which was identified as E.coli O157. Singlepath E.coli O157 examination was applied to confirm the identification of E.coli O157. The results of IMViC and SMAC tests on 12 from 31 samples (38,71%) indicated positive of containing E.coli. Six from 31 samples (19,35%) positively contained E.coli O157. The conclution showed that 19,35% porks from pork traders in Denpasar City were contaminated by E.coli O157. (MEDICINA 2012;43:3-8).